2008
DOI: 10.1103/physrevlett.100.016803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interactions in Transport through Aharonov-Bohm-Casher Interferometers

Abstract: We study the conductance through a ring described by the Hubbard model (such as an array of quantum dots), threaded by a magnetic flux and subject to Rashba spin-orbit coupling (SOC). We develop a formalism that is able to describe the interference effects as well as the Kondo effect when the number of electrons in the ring is odd. In the Kondo regime, the SOC reduces the conductance from the unitary limit, and, in combination with the magnetic flux, the device acts as a spin polarizer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…An important consequence is the existence of the AC oscillations of zero-field conductance G(0) with the strength of the SO coupling. The AC oscillations were intensively discussed theoretically [12][13][14][15][16][17]21,[24][25][26][27][29][30][31][32][33]35 and their signatures were observed experimentally. 22,23 Another consequence, especially important from the point of view of possible applications, is that the unpolarized incoming electron beam acquires polarization after passing through the ring, so that the ring may serve as a spin polarizer.…”
mentioning
confidence: 99%
“…An important consequence is the existence of the AC oscillations of zero-field conductance G(0) with the strength of the SO coupling. The AC oscillations were intensively discussed theoretically [12][13][14][15][16][17]21,[24][25][26][27][29][30][31][32][33]35 and their signatures were observed experimentally. 22,23 Another consequence, especially important from the point of view of possible applications, is that the unpolarized incoming electron beam acquires polarization after passing through the ring, so that the ring may serve as a spin polarizer.…”
mentioning
confidence: 99%
“…This phase is additional with respect to AB phase and exists even at zero external magnetic field (φ = 0) so that zero-field conductance exhibits the Aharonov-Casher (AC) effect: 31,32 periodic oscillations with the strength of the SO coupling. The AC oscillations were the focus of intensive theoretical [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] research and their signatures were observed experimentally. 50,51 Recently, we demonstrated that these oscillations are also not suppressed by thermal averaging, 52 in a full analogy with the AB ones.…”
Section: 2mentioning
confidence: 99%
“…In QD structures, the RSO interaction give rises to an extra spin-dependent phase factor in the coupling matrix elements between the leads and the QD and the inter-level spin-flip term [10]. Hence, the RSO interaction makes the quantum transport phenomena rich and complicated [9]. Recently, Vernek et al [10] theoretically predicted that the combination of RSO interaction and the Aharonov-Bohm (AB) effect strongly suppresses the Kondo resonance, and Lim et al [11] found…”
mentioning
confidence: 96%